Mitochondrial Dynamics and VMP1-Related Selective Mitophagy in Experimental Acute Pancreatitis - Vanasco, Virginia; Ropolo, Alejandro; Grasso, Daniel; Ojeda, Diego S.; García, María Noé; Vico, Tamara A.; Orquera, Tamara; Quarleri, Jorge; Alvarez, Silvia; Vaccaro, María I. (Frontiers in Cell and Developmental Biology, 2021)
Mitophagy and zymophagy are selective autophagy pathways early induced in acute pancreatitis that may explain the mild, auto limited and more frequent clinical presentation of this disease. Adequate mitochondrial bioenergetics are necessary for cellular restoration mechanisms that are triggered during the mild disease. However, mitochondria and zymogen contents are direct targets of damage in acute pancreatitis. Cellular survival depends on the recovering possibility of mitochondrial function and efficient clearance of damaged mitochondria. This work aimed to analyze mitochondrial dynamics and function during selective autophagy in pancreatic acinar cells during mild experimental pancreatitis in rats. Also, using a cell model under the hyperstimulation of the G-coupled receptor for CCK (CCK-R), we aimed to investigate the mechanisms involved in these processes in the context of zymophagy. We found that during acute pancreatitis mitochondrial O2 consumption and ATP production significantly decreased early after induction of acute pancreatitis, with a consequent decrease in ATP/O ratio. Mitochondrial dysfunction was accompanied by changes in mitochondrial dynamics evidenced by optic atrophy 1 (OPA-1) and dynamin-related protein 1 (DRP-1) differential expression and ultrastructural features of mitochondrial fission, mitochondrial elongation and mitophagy during the acute phase of experimental mild pancreatitis in rats. Mitophagy was also evaluated by confocal assay after transfection with the pMITO-RFP-GFP plasmid that specifically labels autophagic degradation of mitochondria and the expression and redistribution of the ubiquitin ligase Parkin1. Moreover, we report for the first time that vacuole membrane protein-1 (VMP1) is involved and required in the mitophagy process during acute pancreatitis, observable not only by repositioning around specific mitochondrial populations, but also by detection of mitochondria in autophagosomes specifically isolated with anti-VMP1 antibodies as well. Also, VMP1 downregulation avoided mitochondrial degradation confirming that VMP1 expression is required for mitophagy during acute pancreatitis. In conclusion, we identified a novel DRP1-Parkin1-VMP1 selective autophagy pathway, which mediates the selective degradation of damaged mitochondria by mitophagy in acute pancreatitis. The understanding of the molecular mechanisms involved to restore mitochondrial function, such as mitochondrial dynamics and mitophagy, could be relevant in the development of novel therapeutic strategies in acute pancreatitis.